Current status and trends in on-farm performance testing of cattle and sheep in Africa - Peters, Kurt J.; Thorpe, W.R. (Institut National de la Recherche Agronomique, 1988)
Reviews the regionalisation of sheep and cattle population in Africa, their association to the various production systems, and output expectation, current levels of performance and constraints. Discusses needs & objectives of performance testing in the region, evaluating advantages & disadvantages of on-farm and on-station performance recording as well as past & present trends in performance testing. Outlines solutions to on farm and on-station testing constraints.